Pagodane—Solution and Solid-State Vibrational Spectra - Stewart F. Parker; Hannah E. Mason; Campbell T. Wilson; Adam J. Jackson (Physchem)
In the present study, we report infrared and Raman spectra in both solution and the solid state, together with a state-of-the art inelastic neutron scattering spectrum, of the unusual molecule pagodane. Periodic DFT calculations have enabled a complete assignment of all the modes. The isolated molecule has D2h symmetry, which is reduced to Ci in the solid state. However, the preservation of the centre of symmetry means that the selection rules for infrared and Raman spectroscopy are almost unchanged. The exceptions are the D2hAu modes that are forbidden in the isolated molecule but become allowed in the solid state. These have been located in the solid-state spectra.